Hydrolytic Studies on Fir (Abies webbiana) and Spr Uce (Picea smithiana) - Karnik, M. G.; Bhatia, Kuldip; Lal, Jia (Indian Forester, 1966)
The partial and total saccharification of the fir and spruce woods were carried out using sulphuric acid as hydrolysing agent. The potential reducing sugar yields and the constituent sugars were determined.